2‐Arachidonoyl glycerol suppresses gastric emptying via the cannabinoid receptor 1‐cholecystokinin signaling pathway in mice. Issue 3 (10th March 2022) - Ochiai, Keita; Hirooka, Rina; Sakaino, Masayoshi; Takeuchi, Shigeo; Hira, Tohru
Abstract: 2‐Monoacylglycerol (2‐MAG) is one of the digestion products of dietary lipids. We recently demonstrated that a 2‐MAG, 2‐arachidonoyl glycerol (2‐AG) potently stimulated cholecystokinin (CCK) secretion via cannabinoid receptor 1 (CB1) in a murine CCK‐producing cell line, STC‐1. CCK plays a crucial role in suppressing postprandial gastric emptying. To examine the effect of 2‐AG on gastric emptying, we performed acetaminophen and phenol red recovery tests under oral or intraperitoneal administration of 2‐AG in mice. Orally administered 2‐AG (25 mg/kg) suppressed the gastric emptying rate in mice, as determined by the acetaminophen absorption test and phenol red recovery test. Intraperitoneal administration of a cholecystokinin A receptor antagonist (0.5 mg/kg) attenuated the gastric inhibitory emptying effect. In addition, both oral (10 mg/kg) and intraperitoneal (0.5 mg/kg) administration of a CB1 antagonist counteracted the 2‐AG‐induced gastric inhibitory effect. Furthermore, intraperitoneal 2‐AG (25 mg/kg) suppressed gastric emptying. These results indicate that 2‐AG exhibits an inhibitory effect on gastric emptying in mice, possibly mediated by stimulating both CCK secretion via CB1 expressed in CCK‐producing cells and acting on CB1 expressed in the peripheral nerves. Our findings provide novel insights into the 2‐MAG‐sensing mechanism in enteroendocrine cells and the physiological role of 2‐MAG.